Development of Online Service Booking Mobile Application Using Android Studio (International Journal of Innovative Research in Engineering & Management, 2022)
This research is all about an application  developed in order to make household services more  manageable and easy like never before. We have developed  an application for Online Service Booking native android  application using android studio new version. This paper will  also describe the working principle of this app. Admin panel  of the application has been developed in PHP language with  the help of Code Igniter framework a perfect tool to develop  this kind of application. PHPMYADMIN has been used for  the development of the database. Also we have used the  hosting facility provided by 000webhost to deploy our code  onto the server. Google firebase has been used for connecting  our both the application as well as the admin panel all  together. This application has many type of services. User  can choose services according to their need and convenience.
Keywords: Android Studio; Service Booking; Application; ServiceBoy Application; Admin Panel; CodeIgniter